GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 237658 species occurrences available in GBIF matching the query: TaxonKey: Fragaria L.. The dataset includes 237658 records from 714 constituent datasets: 4 records from Bioimages. 2 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 124 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 3 records from JOI - Herbário Joinvillea. 1 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2 records from OEH Atlas of NSW Wildlife. 694 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 16594 records from Botanical Society of the British Isles - Vascular Plants Database. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 4 records from HUFU - Herbarium Uberlandense. 1022 records from Phanerogamic Botanical Collections (S). 428 records from Jordal. 1 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 12 records from University of Vienna, Institute for Botany - Herbarium WU. 61 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 573 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 544 records from Consortium of California Herbaria. 115 records from Online Atlas of vascular plants 2012-2020. 49 records from IAC - Herbário do Instituto Agronômico de Campinas. 2 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 24 records from Herbarium Vonderau - FULD. 156 records from Herbarium WRSL, Flora of the Silesia. 243 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 2164 records from Naturalis Biodiversity Center (NL) - Botany. 29 records from PlutoF platform observations. 4 records from SPSF - Herbário Dom Bento José Pickel. 6 records from PRECIS. 88 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 1 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 217 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 382 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 27 records from SANT herbarium vascular plants collection. 2 records from Collection du Musée d'Histoire Naturelle de Nice. 292 records from Harriet Irving Botanical Gardens (HIBG). 22 records from Species plots from the Norwegian Vegetation Mapping Programme. 3 records from Colección Herbario Federico Medem Bogotá - FMB. 10 records from Local BioBlitz Challenge 2013. 813 records from FLORIVON. 8 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 657 records from Species data extracted from the National Vegetation Database. 1113 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 1 records from Herbario Pontificia Universidad Javeriana. 3 records from ICN - Herbário do Instituto de Ciências Naturais. 1 records from Herbario Universidad de Antioquia (HUA). 323 records from University of Alberta Vascular Plant Herbarium (ALTA). 162 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 2010 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 68 records from The digitization of plant specimens of NTU. 59 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 306 records from Phytochorologie des départements français. 1 records from SMDB - Santa Maria Departamento de Biologia. 767 records from BioFokus. 1 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 245 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 134 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 2 records from CESJ - Herbário Leopoldo Krieger. 85 records from Irish Vascular Plant Data - Paul Green. 7758 records from FlorKart - FlorenKartierung Gefaesspflanzen. 41 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 7 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 23508 records from Artdata. 3 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 35 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 8 records from Herbario Museo de La Salle Bogotá (MLS). 1 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 470 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 384 records from OHN. 2 records from Especímenes INBio. 1 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 49 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 2290 records from Données ONF Faune-Flore-Fonge. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 1 records from FCAB - Herbário Friburguense. 6 records from Tallinn Botanic Garden. 36 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 1 records from Herbarium areqvipense (HUSA). 3 records from Plant observations from Białowieża National Park. 25 records from Norwegian Biodiversity Information Centre - Other datasets. 29 records from Australia's Virtual Herbarium. 1287 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 89 records from Herbier de Strasbourg. 310 records from Vascular Plant Herbarium, UiB. 48 records from Kathryn Kalmbach Herbarium. 281 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 15 records from Natural History Museum Maastricht (NL) - Herbarium. 889 records from Consortium of California Herbaria. 402 records from iNaturalist research-grade observations. 22 records from UCBG TAPIR Provider. 549 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 190 records from CONN. 13 records from HUCS - Herbário da Universidade de Caxias do Sul. 109 records from H.A. Stephens Herbarium. 1 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 95 records from University of Lethbridge Herbarium (LEA). 32 records from Louisiana State University Herbarium - Vascular Plants. 229 records from UCJEPS TAPIR Provider. 140 records from Estonian Museum of Natural History. 1 records from minsok. 5 records from Collection botanique Le Grand A. (BOUM). 1 records from University of California Museum of Paleontology. 40 records from NINA botanical collection. 8 records from ALCB - Herbário Alexandre Leal Costa. 332 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 14 records from HPBR - Herbário Padre Balduino Rambo. 3 records from Herbarium Rhoenmuseum Fladungen. 224 records from Estonian University of Life Sciences. 55 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 212 records from NMNH occurrence DwC-A. 1 records from FNL e.V.. 1 records from Beweidungsprojekt an der Nesse. 1 records from Kloster Eberbach. 1 records from Waldsee. 1 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 5 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 1 records from Truppenübungsplatz Panzerkaserne Böblingen. 1 records from Schulgarten mit Klasse 8a (Essen). 1 records from Döchtbühlwald (Bad Waldsee). 1 records from Artenvielfalt Kreis Gießen. 1 records from Regenrückhaltebecken (Zeulenroda). 1 records from Zielbach (Töll). 1 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 1 records from Südpark (Bochum-Wattenscheid). 1 records from Bodenseeufer Radolfzell. 1 records from Zitadelle Berlin-Spandau (7b). 1 records from Steinbruch Mainz-Weisenau. 1 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 1 records from Triebesbach (Zeulenroda-Triebes). 1 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 1 records from Umgebung der Grundschule Oderberg. 3 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Paul-Gerhardt-Schule Dassel. 2 records from privater Garten. 1 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 1 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 1 records from Alter Kreidebruch Saßnitz/Rügen. 1 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 1 records from Rund um das LUGY. 1 records from Landschaftsschutzgebiet Buchhorst 3. 1 records from Varnhalt. 1 records from Rund ums Ökohaus (Würzburg). 1 records from Brander Wald (Stolberg). 1 records from Balkon (Norderstedt). 1 records from Spießwoogtal / Königsbruch (Fischbach). 1 records from Urwald 3 (Bad Waldsee). 1 records from Wiese und Bach beim Unterbecken (Markersbach). 2 records from Garten J. Scherrer (Lachen-Speyerdorf). 1 records from Außengelände KITA "Mäuseburg" Waldkirchen. 1 records from Obstwiese Osterberg. 1 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 1 records from Oschenberg, NO von Bayreuth-Laineck. 1 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 1 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 1 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 1 records from Gieselbachtal Fulda-Harmerz. 1 records from Hainbachtal bei Oelsnitz / V.. 1 records from Vielfalt verschiedener Wiesen. 1 records from Bammentaler Duft- und Heilkräutergarten. 1 records from Grillhütte Wettsaasen, Wiese, Hecken. 1 records from Weidewirtschaft. 1 records from Birkenloh. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 2 records from vegoek. 1 records from Gelände des Schulzentrums am Himmelsbarg. 1 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 2 records from Klütwald. 1 records from Schrebergarten Düsseldorf Oberkassel. 1 records from Dörnberg. 1 records from Naturschutzgebiet Kochertgraben. 1 records from Hoher Stein Kallenhardt. 1 records from Mauervegetation,Flechten und anderes. 1 records from Rotes Steigle (Panzerübungplatz Böblingen). 1 records from Tiere und Pflanzen am Pfannenbach. 1 records from FFH-Gebiet "Calwer Heckengäu". 1 records from Landschaftsschutzgebiet Schmutterwald. 2 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from Bannwald Burghauser Forst. 1 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 1 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 1 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 1 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 2 records from Pöhlberg bei Annaberg. 3 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 1 records from Haarbach Höfe. 1 records from Schulzentrum "Parc Hosingen". 1 records from Bernhardsthal. 2 records from VFD-RP: Eifel: Orchideenweide Ankly. 1 records from Weinberg Reichersdorf. 1 records from Naturschutzgebiet Börstig bei Hallstadt. 1 records from Tag der Artenvielfalt in Heidelberg. 2 records from Lustbach-Umland. 1 records from Königsdorfer Wald. 1 records from Owere Fiddel. 1 records from NSG Forst Zinna-Jüterbog-Keilberg. 1 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 2 records from Tornoer Teich. 1 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 2 records from Liether Kalkgrube. 1 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 2 records from Schulgarten der Volksschule. 1 records from Sürther Aue. 1 records from Aachtobel. 1 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 1 records from Wälder im Hainbachtal. 1 records from Steinbruch Kronungen. 1 records from Ober-Olmer Wald. 1 records from Rund um den Hainbergsee. 1 records from VFD-H: Heidenrod: Weide am Ortsrand. 1 records from "Ahrschleife bei Altenahr". 1 records from Pflanzen und Tiere im Burgwald. 1 records from VFD-H.: Rheingau: Bärstadt. 1 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 1 records from Unter hellen Zinnen und finsteren Grotten. 1 records from Aktion der Klasse H2 in Simmelsberg. 1 records from Reusaer Wald. 1 records from Teich im Wald zwischen Böblingen und Schönaich. 22 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 2 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 38 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 16 records from Ireland's BioBlitz 2012. 119 records from OAC-BIO Herbarium. 169 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 21 records from Herbario de la Universidad de Granada: GDA. 1628 records from naturgucker. 12 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 7 records from National Trust - Hatfield Forest species data held by The National Trust.. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 2 records from Freiburger GEO-Tag der Artenvielfalt. 3 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from Kühmark bei Wetzlar. 1 records from Eschlberg Thalhausen. 1 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Sahrbachtal Kreis Ahrweiler. 1 records from Baggerseen bei Krauchenwies. 1 records from Schriesheimer Steinbruch. 1 records from Mangfalltal. 2 records from LBV 100 - Artenvielfalt am Rothsee. 1 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Aktion - Friedensburg Oberschule. 1 records from Artenvielfalt auf Zollverein. 1 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 1 records from Biotope in Rheine - Aktion 350. 2 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 4 records from Butterberg, Dardesheim. 1 records from Nationalpark Jasmund. 1 records from Bulau. 2 records from Luderbusch. 1 records from Werl macht sich auf die Suche. 1 records from Rur. 1 records from Mönchspark. 1 records from Wälder bei Nordkirchen. 1 records from BB-Biodiversität b. 1 records from Projekt Dellbrücker Heide. 1 records from Rund um die Sausenburg. 1 records from Bayerische Donau - Blindheim Donaubrücke. 1 records from Schloss Fasanerie Eichenzell. 1 records from Streuobstwiese Stedar 2009. 1 records from Schieferbrüche. 1 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 1 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 1 records from Naturpark Sternberger Seenland. 1 records from Stadtwald Heide. 1 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 1 records from Naturpark Kottenforst-Ville 17.6.09. 1 records from Raus in die Natur. 1 records from Pfingstexkursion Alter Bessin. 1 records from Artenvielfalt vor unserer Kita-Haustür. 1 records from Naturschutzgebiet Lüneburger Heide. 3 records from MfN - Fossil plants (Cenophytic). 488 records from The Flora of County Wexford. 2335 records from Dutch Vegetation Database (LVD). 53166 records from INPN - Données flore des CBN agrégées par la FCBN. 4 records from UEC - Herbário da Universidade Estadual de Campinas. 12 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 4 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 5 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 46 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 42 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 14 records from Herbario del CIBNOR. 38 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 7 records from Jardin botanique de Montréal (JBM). 1 records from Fliegenhaupt Marksuhl. 1 records from Flora und Fauna im Brexbachtal. 1 records from Kindervilla Aussengelände/ Hiltroper Park. 1 records from Neißetal. 1 records from Ober-Olmer Wald 09. 1 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 15 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 32 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 22 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 1 records from Plant (JNHM-PL). 9 records from Plant (MNHM-PL). 2 records from Plant (NSMK-PL). 4 records from Herbaria of the University and ETH Zürich. 2 records from Mongolian Plant (MMNH-PL). 1 records from Collection botanique Mulon L. (BOUM). 27 records from Tiroler Landesmuseum Ferdinandeum. 3 records from The Fungal Collection at the Botanische Staatssammlung München. 1170 records from IBF Monitoring of Vascular Plants. 1 records from Vascular plant specimens of Iida City Museum. 699 records from BSBI tetrad data for Ireland. 503 records from Missouri Botanical Garden. 1 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 47 records from Natural History Museum (London) Collection Specimens. 137 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 2 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 123 records from Natural History Museum, Vienna - Herbarium W. 1 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 9 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 79 records from NatureServe Network Species Occurrence Data. 71 records from Flora-On: occurrence data of the flora of mainland Portugal. 7 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 4 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 72 records from Ireland's BioBlitz. 297 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 8 records from Base de datos sobre la flora de Durango. 1 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 5 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 12 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 16 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 2 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 356 records from Dataflos. 26 records from Ibaraki Nature Museum, Vascular Plants collection. 23 records from Leiner-Herbar Konstanz. 2 records from Universität Salzburg. 307 records from Herbarium, Centre for Biodiversity, University of Turku, Finland (TUR). 899 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 28 records from Herbarium (Åbo Akademi), Centre for Biodiversity, University of Turku (TURA). 152 records from The Himalayan Uplands Plant database (HUP Version 1). 12760 records from Herbarium, Botany Unit, Finnish Museum of Natural History (H). 1 records from Australian National Herbarium (CANB). 8 records from Botanical Garden Collection. 1 records from Korean Ethnobotany Database. 31 records from Canadian Museum of Nature Herbarium. 379 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 2 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 20 records from The AAU Herbarium Database. 141 records from Herbarium (ICEL). 31 records from Herbarium (AMNH). 221 records from Observational database of Icelandic plants. 62 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 45 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 83 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 17 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 1 records from Herbario de la Universidad de Almeria. 21 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 78 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 6 records from Jardín Botánico de Córdoba: Herbarium COA. 38 records from Aranzadi Zientzi Elkartea. 2 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 10 records from Universitat de Girona: HGI-Cormophyta. 8 records from CIBIO, Alicante:ABH-GBIF. 12 records from GBIF-PORTUGAL-Herbário João de Carvalho e Vasconcellos, I.S.A./U.T.L.. 6 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 7 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 43 records from Herbario de la Universidad de Sevilla. 5 records from Herbario de la Universidad de Sevilla, SEV-Historico. 21 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 4 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 17 records from Institut Botanic de Barcelona, BC. 3 records from Hortus Botanicus Sollerensis Herbarium (FBonafè). 17 records from Botanic Garden of the Finnish Museum of Natural History. 227 records from Herbarium of Jyväskylä University Museum. 2 records from Plant in Baekdu Mountain (KIDR-PL). 46 records from Royal Botanical Gardens Herbarium. 9 records from DAO Herbarium Type Specimens. 2 records from Paleobiology Database. 7 records from herbario. 2 records from Plant Specimens of Kurashiki Museum of Natural History. 1 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 381 records from Vascular Plant Collection. 46 records from Arizona State University Vascular Plant Herbarium. 7 records from University of Copenhagen Arboretum. 27 records from Botany registration database by Danish botanists. 2 records from Botanical Museum, Copenhagen. Database of type specimens. 65 records from Database Schema for UC Davis [Herbarium Labels]. 88 records from California State University, Chico. 10 records from Herbarium (UNA). 4 records from MEXU/Plantas Vasculares. 4 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 1 records from NSW herbarium collection. 1 records from Plants of Papua New Guinea. 6 records from Flora exsiccata Bavarica. 74 records from Herbarium Berolinense. 85 records from Herbarium Willing. 25 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 16634 records from Observations du Conservatoire botanique national du Bassin parisien.. 149 records from Biologiezentrum Linz. 90 records from Herbarium Senckenbergianum Görlitz (GLM). 1831 records from United States National Plant Germplasm System Collection. 8 records from The Erysiphales Collection at the Botanische Staatssammlung München. 1 records from The Erysiphales Collection at the University Halle-Wittenberg. 2 records from Water Colours of Fungi by Konrad Schieferdecker at the Botanische Staatssammlung München. 3 records from Nordic Genetic Resources. 124 records from USU-UTC Specimen Database. 1 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 4 records from Institut Botanic de Barcelona, BC-Histórico. 16 records from Herbarium de Geo. B. Hinton, México. 8141 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 6 records from Angiosperm specimens of Iwate Prefectural Museum. 9 records from Vascular Plants Collection of Sagamihara City Museum. 388 records from Harvard University Herbaria. 34 records from Vascular plants of south-central China. 122 records from Specimen Database of Colorado Vascular Plants. 51 records from Herbarium BSG Vascular Plants. 32 records from inatura - Erlebnis Naturschau Dornbirn. 2447 records from EURISCO, The European Genetic Resources Search Catalogue. 14 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 19 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 4 records from Kochi Prefectural Makino Botanical Garden. 9 records from Plant (MNHM-PL). 1 records from MAR - Herbário do Maranhão. 144 records from Flora d'Andorra. 206 records from Staffordshire Ecological Record - SER Site-based Surveys. 569 records from Biodiversitätsdatenbank des Landes Salzburg. 4 records from Herbario de la Universidad de Arizona, EUA. 18 records from Repatriación de datos del Herbario de Arizona (ARIZ). 4 records from Vascular Plants, Observations, Oslo (O). 91 records from Oklahoma Vascular Plants Database Provider. 373 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from BÜG. 1 records from Überall ist Wunderland. 1 records from DJH. 1 records from Streuobstwiese RSG (Cham). 1 records from AKG-Gelände (Bensheim). 1 records from FFH-Gebiet Ahrbachtal. 1 records from Botanischer Garten (Saarbrücken). 1 records from Trockenhang Greinhartsberg Edelfingen. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Hamberger Brücke / Würmtal (Pforzheim). 2 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 1 records from Kernberge und Umgebung (Jena). 1 records from Schlichemquelle (Tieringen/Meßstetten). 1 records from Mooswald (Freiburg). 1 records from Gemeinde Sursee. 1 records from Gewann Krampf (Heilbronn). 1 records from Naturschutzstation Schmidsfelden. 1 records from Landschaftspflegehof (Berlin). 1 records from Naturschutzgebiet Bausenberg. 2 records from Schlern - (Bozen). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 2 records from Schule Sulzbach (Oberegg). 3 records from Königstetten. 1 records from Frauenholz (Holzmaden). 1 records from Freiburger Tag der Artenvielfalt. 1 records from Erzental (Oberotterbach). 1 records from Langes Tannen (Uetersen). 2 records from Gelände des IVL (Zeckern). 1 records from Stausee (Oberdigisheim/Meßstetten). 1 records from Naturschutzgebiet Bausenberg (Niederzissen). 2 records from Erlengraben/Lipp-Tal (Östringen). 1 records from Wald und Wiese am Buchwald. 2 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 1 records from NSG Karwendel. 1 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 2 records from Neckartalsüdhang (Horb). 1 records from Schulgarten Huttenheim (Philippsburg/Baden). 1 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 1 records from Wiese und Weide am Waldrand von Gusterath. 1 records from Umgebung von Schorndorf. 2 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 2 records from nazza. 1 records from katzenbuckel. 1 records from Promberg1. 2 records from GEO-Hauptveranstaltung (Duisburg). 1 records from BUND - Dassower See (Lübeck/Dassow). 1 records from Wildes Bremer Leben im Park. 1 records from Luch Niederlehme, Schüler der Klasse 7. 1 records from Pilstingermoos. 1 records from Artenfülle um das Schalkenmehrener Maar. 1 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 2 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 1 records from Gurgltal (Tarrenz). 1 records from Überschwemmungsgebiet der Wied. 2 records from 20 Jahre Naturschutzgebiet Dreienberg. 1 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 1 records from 4. GEO-Tag in Eberbach. 2 records from schulgarten. 1 records from Pottundkopp. 1 records from Knechtweide (Kohlfurth). 1 records from Schulumgebung Grüterschule, Rheine. 1 records from Wald am Schloss Wittgenstein Bad Laasphe. 1 records from Bergbaufolgelandschaft am Muldestausee. 1 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 1 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Schulhof Goethe-Gymnasium (Emmendingen). 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from NSG Berschau - Auengebiet (Neustadt / Wied). 2 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Unser Schulhof - eine Apotheke. 1 records from Faberpark (Nürnberg/Stein). 1 records from Streuobstwiese Kugelberg (Ulm). 2 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 1 records from Wiese am Waldrand (Gurtweil). 1 records from Urwald 1 (Bad Waldsee). 1 records from Fuldaaue (Stadtgebiet Fulda). 2 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Stadt Königs Wusterhausen. 1 records from Schulhof und Anlagensee in Nellingen. 1 records from Werremündung im Schwarzatal. 1 records from Schlattstaller Tal (Lenningen). 2 records from Naturschutzgebiet Müchelholz (Mücheln). 6 records from Eppingen und Umgebung. 1 records from Steinbruch Haas Stuttgart-Münster. 1 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 1 records from renaturierter Main (Kemmern bei Bamberg). 1 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 1 records from Steinbruch Pluwig. 1 records from Lebensraum Stadt und Park. 1 records from Wupperaue bei Kemna (Wuppertal). 1 records from Dreilinden Gymnasium-Schulgelände. 1 records from Altenburg bei Bamberg. 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 1 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from Mißmahlsche Anlage. 1 records from Schulgelände Städtisches Gymnasium. 1 records from Schulgelände SGD/Viersen. 55 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 223 records from Natural History Museum, University of Tartu. 47 records from Herbarium of Umeå University (UME). 208 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 110 records from Field Museum of Natural History (Botany) Seed Plant Collection. 3 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 3121 records from Belgian IFBL Flora Checklists (1939-1971). 5731 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 226 records from New Mexico Biodiversity Collections Consortium database. 3 records from Perchtoldsdorfer Heide. 1 records from Naturpark Drömling. 1 records from Schwanheimer Wald. 1 records from Freiburger Netzwerk Artenvielfalt. 1 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 1 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 1 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 1 records from Biosphärenreservat Münsinger Alb. 79 records from Colorado State University Herbarium. 1 records from EKY_Darwincore. 16 records from MISS_DC_01MAR2006. 74 records from UA Herbarium. 1 records from Lustadter Wald .. 1 records from Kohlstattbrunnental. 137 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1 records from EDIT - ATBI in Gemer area (Slovakia). 138 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 5 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 2 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 29 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 27 records from Gunma Museum of Natural History, Vascular Plant Specimen. 2 records from Vascular plants collection of Hiratsuka City Museum. 2 records from Artenvielfalt am Schlern. 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 1 records from VFD-BW, Dinkelberg: Pferdeweiden Oberminseln. 1 records from VFD-BW, Oberrhein/Schwarzwaldrand: Pferdeweiden Liel. 1 records from VFD-BW, Schwäbische Alb: Pferdeweiden Zainingen. 1 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 101 records from Plant. 13 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 943 records from Biological and palaeontological collection and observation data MNHNL. 109 records from Botany Division, Yale Peabody Museum. 1 records from Tag der Artenvielfalt im Taubental. 1 records from Collection Pisces SMF. 52 records from Herbarium Senckenbergianum (FR). 19 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 39 records from Database of Native Plants in Taiwan. 1 records from University of Ghana - Ghana Herbarium. 2 records from Plant of Folklore (KIDR-PL). 23 records from Herbarium of Taiwan Forestry Research Institute. 14 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 2 records from WII Herbarium Dataset. 42 records from National vegetation diversity inventory and mapping plan. 44 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 9 records from Vascular Herbarium, NMBU. 29 records from Wetland Inventory (NV). 2 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 5 records from UPCB - Herbário do Departamento de Botânica. 10 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 20 records from Faun. 8 records from National System of Protected Areas in Poland - Plants. 1 records from Plant (JNHM-PL). 30 records from ArtenFinder. 261 records from Lund Botanical Museum (LD). 2 records from National Trust - Ickworth species data held by The National Trust.. 4972 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 22 records from Geographically tagged INSDC sequences. 39 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 68 records from Fieldjournal.org observation database. 17 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 9744 records from Norwegian Species Observation Service. 61 records from Irish vascular plant data 1999-2009. 142 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 15 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 34 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 1771 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 7 records from Wildlife Sightings. 38 records from SBT-Living. 8 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 104 records from Bernice P. Bishop Museum. 1 records from FURB - Herbário Dr. Roberto Miguel Klein. 2 records from Mongolian Plant (MMNH-PL). 129 records from Irish Crop Wild Relative Database. 368 records from Carnet en Ligne. 11 records from Botanical Society of the British Isles - SNH Site Condition Monitoring - Vascular plants (2000-2006). 1 records from CRI - Herbário Pe. Dr. Raulino Reitz. 164 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 10 records from Staffordshire Ecological Record - SER Species-based Surveys. 1 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 5 records from Seed collection – Dead seeds for evaluation and observation purposes. 34 records from Tullie House Museum - Tullie House Museum. Cumbria Wildlife Trust survey records from 1970 - 2007 of Cumbria Wildlife Sites. Various.. 488 records from The Flora of County Wexford. 9 records from Colección del Herbario PSO de la Universidad de Nariño. 324 records from Royal Botanic Garden Edinburgh Herbarium (E). 209 records from Michigan State University Herbarium Vascular Plants. 32 records from Herbier du Muséum Henri-Lecoq de Clermont-Ferrand - Rosacées. 157 records from Flora of County Cavan. 187 records from Botany (UPS). 32 records from Instituto de Ciencias Naturales. 1422 records from National Forest Inventory (SLU). 20 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 28 records from University of British Columbia Botanical Garden Collections (UBCBG). 29 records from Estonian Nature Observations Database. 457 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 2 records from JPB - Herbário Lauro Pires Xavier. 616 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 15 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 52 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 1 records from Herbario de la Universidad Industrial de Santander. 2 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 1 records from R - Herbário do Museu Nacional. 44 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 7 records from The Flora of County Clare. 3 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 208 records from Tromsø Museum, Vascular plants. 5 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 250 records from Vascular Plant Herbarium, Trondheim (TRH). 2290 records from Données ONF Faune-Flore-FOnge. 69 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 1 records from New Zealand Biodiversity Recording Network. 4935 records from Vascular Plants, Field notes, Oslo (O). 196 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 3285 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 281 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 2 records from Plant (NSMK-PL). 2 records from Nijmegen Natural History Museum (NL) – Herbarium. 2 records from Wilson Botanical Garden - Las Cruces Biological Station. 34 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 6 records from Ecofact. 1 records from UB - Herbário da Universidade de Brasília. 87 records from Green Plant Herbarium (TRT). 1 records from Colección Herbario Universidad Católica de Oriente. 353 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 102 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 3 records from Instituto de ciencias naturales. 1 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 4 records from Miscellaneous Vascular Plants. 14 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 1022 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 23 records from Allan Herbarium (CHR). 3 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 185 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 154 records from SysTax - Botanical Gardens. 3 records from Herbarium of University of Białystok - Vascular Plants. 126 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 618 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 6 records from Herbarium specimens of CBNA (GAP). 476 records from Flore de Franche-Comté. 2 records from BioFresh Pond Data. 2 records from HPL - Herbário do Jardim Botânico Plantarum. 79 records from CZE National PGR Inventory. 60 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 1317 records from Vascular Plant Herbarium, Oslo (O). 1 records from Occurrences in SinBIOTA. 9 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 77 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 11 records from Anymals+plants - Citizen Science Data. 13 records from Natural History Museum Rotterdam (NL) - Plantae collection. 5 records from Vascular plants of Amrum 2007-2008. 567 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 99 records from E. C. Smith Herbarium (ACAD). 40 records from BUT Friesner Herbarium. 381 records from The Flora of County Waterford. 32 records from SWECO. 8 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 13 records from Herbarium Erlangense. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 3 records from Herbier Boreal Confluence (BOUM). 7 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 782 records from Vascular Plants, Field notes, Trondheim (TRH). 6 records from SysTax - Herbaria. 17 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 9 records from Geneva Herbarium – General Collection (G). 27 records from Instituto de Botánica Darwinion. 3 records from Nijmegen Natural History Museum (NL) - Herbarium. 482 records from Northern Ireland Environment Agency - EHS Species Datasets. 39 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 1119 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 244 records from Flora of the Stołowe Mts.. 478 records from CAS Botany (BOT). 874 records from Atlas des plantes vasculaires de Lorraine. 12 records from National Museum of Natural Science. 1 records from Herbarium specimens of Limoges university (LIMO). 1 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 9 records from PACA-AGP - Herbarium Anchieta. 205 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups.
Keywords: GBIF; biodiversity; species occurrences